The Implications of Ex-Post Audits for Legal Certainty and the Business Sustainability of Construction Service Providers - Awayakuane, Revolino Robarto; Winarsi, Sri; Kurniawan, Faizal (Universitas Islam Negeri Alauddin Makassar, 2026)
Government construction projects operate under a public financial oversight regime that allows legal and financial consequences to arise after project completion and contractual payment. This study examines the legal implications of ex post audits conducted by the Audit Board of the Republic of Indonesia on legal certainty for construction service providers in government projects and analyzes their effects on business certainty during project implementation. This research is using socio-legal analysis with legal and economic perspectives. The findings indicate that ex post audits consistently generate financial recommendations with values that fluctuate widely across semesters, ranging from tens of billions to tens of trillions of rupiah. These recommendations emerge after construction completion and contractual payment, placing financial and administrative consequences in a retrospective position. Dominant audit indicators include weaknesses in internal control systems, statutory non-compliance, and uneconomical, inefficient, and ineffective use of public funds. This pattern shows that contractual finality in government construction projects depends on audit outcomes and follow-up implementation rather than contractual performance alone. The study indicates that legal and business certainty for construction service providers in government projects develop in a delayed manner under post-execution public financial oversight.